Optimalisasi Produktivitas Kinerja Melalui Keterlibatan Karyawan Aktif Dan Pengurangan Stres dengan Dukungan Manajerial yang Efektif - Aldi Friyatna Dira; Kurniawan Prambudi Utomo; Aprilia Puspasari; Devy Sofyanty (Jurnal Kajian Ilmiah, 2024)
The purpose of this study is to explain optimizing performance productivity through active employee involvement and stress reduction with effective managerial support in the work environment at the company, the research method uses quantitative research and conducts field observations (field research) using the self-administered questionnaires method, namely direct distribution of questionnaires by face-to-face with these respondents using a population of 70 respondents in saturated samples and carried out in March - June 2023 using data analysis using multiple linear regression analysis and distributing questionnaires and interviews and literature studies, after that data processing was carried out with processing analysis SPSS statistical data version 26. The results show that there is a significant relationship and influence both partially and simultaneously that the variable active employee involvement and stress reduction has on managerial support for company productivity so that it needs to be developed and managerial attention to increase company productivity in a sustainable manner in the future.